2018
DOI: 10.1074/jbc.ra118.004475
|View full text |Cite
|
Sign up to set email alerts
|

The labile interactions of cyclic electron flow effector proteins

Abstract: The supramolecular organization of membrane proteins (MPs) is sensitive to environmental changes in photosynthetic organisms. Isolation of MP supercomplexes from the green algae , which are believed to contribute to cyclic electron flow (CEF) between the cytochrome complex (Cyt- ) and photosystem I (PSI), proved difficult. We were unable to isolate a supercomplex containing both Cyt- and PSI because in our hands, most of Cyt- did not comigrate in sucrose density gradients, even upon using chemical cross-linker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 73 publications
(153 reference statements)
1
17
0
Order By: Relevance
“…We then assessed the impact of FNR location on photosynthetic electron transport. Because of the longstanding debate about the role of FNR in CEF ( Bendall and Manasse, 1995 ; Bojko et al, 2003 ; Buchert et al, 2018 ; Hanke et al, 2008 ; Hertle et al, 2013 ; Hosler and Yocum, 1985 ; Iwai et al, 2010 ; Mosebach et al, 2017 ; Shahak et al, 1981 ; Ye and Wang, 1997 ; Zhang et al, 2001 ), and the suggestion that relocation of FNR might be a mechanism to switch between LEF and CEF ( Breyton et al, 2006 ; Joliot and Johnson, 2011 ), we paid particular attention to CEF related parameters. It is reported that rates of CEF are highest in the first 20 s of illumination following dark adaptation ( Joliot and Joliot, 2005 ), and this corresponds to the time scale over which the slow kinetic phase of NADP + reduction kinetics develops ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We then assessed the impact of FNR location on photosynthetic electron transport. Because of the longstanding debate about the role of FNR in CEF ( Bendall and Manasse, 1995 ; Bojko et al, 2003 ; Buchert et al, 2018 ; Hanke et al, 2008 ; Hertle et al, 2013 ; Hosler and Yocum, 1985 ; Iwai et al, 2010 ; Mosebach et al, 2017 ; Shahak et al, 1981 ; Ye and Wang, 1997 ; Zhang et al, 2001 ), and the suggestion that relocation of FNR might be a mechanism to switch between LEF and CEF ( Breyton et al, 2006 ; Joliot and Johnson, 2011 ), we paid particular attention to CEF related parameters. It is reported that rates of CEF are highest in the first 20 s of illumination following dark adaptation ( Joliot and Joliot, 2005 ), and this corresponds to the time scale over which the slow kinetic phase of NADP + reduction kinetics develops ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the literature investigating a role for FNR activity in CEF is extensive, with multiple inhibitor based studies supporting this hypothesis ( Ravenel et al, 1994 ; Shahak et al, 1981 ; Bendall and Manasse, 1995 ; Mills et al, 1979 ; Cleland and Bendall, 1992 ; Ye and Wang, 1997 ; Hosler and Yocum, 1985 ). The actual function for FNR in higher plant CEF, however, remains speculative: it has been proposed as a direct Fd:quinone reductase ( Bojko et al, 2003 ), or as a binding site for Fd to allow reduction of quinones via PgrL1 ( Hertle et al, 2013 ) or the Cyt b 6 f in both algae and higher plants ( Buchert et al, 2018 ; Zhang et al, 2001 ; Buchert et al, 2020 ). Although it is reported that interaction with Tic62 or TROL has no impact on FNR activity ( Alte et al, 2010 ), another possibility is that by binding to Tic62 or TROL, FNR becomes less efficient at oxidising Fd.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, stt7-9 still contained the phosphorylation(s) in the b6f that might be responsible for the AA sensitivity 10 . We showed that candidate phosphorylation sites are found in the stromal region of the interacting subunit-IV and PETO, the loosely attached CEF effector 10,11,12,16 . Furthermore, the CEF rates in stt7-9 were obtained in the presence of DCMU .…”
Section: Discussionmentioning
confidence: 98%
“…The comparable initial rates might be distantly related to findings in Arabidopsis pgr5 showing WT-like CEF during the induction phase, despite a different CEF regulation capacity in pgr5 42 . It was demonstrated in Chlamydomonas that Fd-binding proteins PETO and ANR1 interact with the b6f, and at least PETO has access to the stromal b6f region 12,43,44 . If these interactions are PGR5-independent, a pool of Fd may be retained in proximity of the algal Qi-site by these auxiliary CEF proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation